2009
DOI: 10.1111/j.1365-2753.2008.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking‐cessation therapy using varenicline: the cost‐utility of an additional 12‐week course of varenicline for the maintenance of smoking abstinence

Abstract: An additional 12-week course of varenicline treatment, provided to abstainers after an initial 12-week treatment, produces relatively low incremental cost-utility ratios in the spectrum of life-saving medical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…89 Other previous applications of the BENESCO model have used non-UK populations and parameter inputs, making comparison of total LYs and QALYs difficult. [62][63][64][66][67][68][69][70][71][72]89 However, results across these studies and here have been similar, in that the intervention with the greatest clinical effectiveness (short-term cessation probability) has consistently had the greatest cost-utility.…”
Section: Discussion On Modelling Aspectsmentioning
confidence: 55%
See 1 more Smart Citation
“…89 Other previous applications of the BENESCO model have used non-UK populations and parameter inputs, making comparison of total LYs and QALYs difficult. [62][63][64][66][67][68][69][70][71][72]89 However, results across these studies and here have been similar, in that the intervention with the greatest clinical effectiveness (short-term cessation probability) has consistently had the greatest cost-utility.…”
Section: Discussion On Modelling Aspectsmentioning
confidence: 55%
“…The BENESCO model has been used in numerous previous evaluations. [63][64][65][66][67][68][69][70][71][72][73] The model uses an annual cycle length and assumes that all smokers die at age 100 years, if death has not been simulated at an earlier age. A hypothetical cohort of 10,000 smokers enters the model, with each smoker assumed to make a single quit attempt, assisted by either varenicline or cytisine.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation